Isoxaflutole and metribuzin interactions in isoxaflutole-resistant soybean. Issue 5 (26th June 2019) - Smith, Andrea; Soltani, Nader; Kaastra, Allan C.; Hooker, David C.; Robinson, Darren E.; Sikkema, Peter H.
Abstract: Herbicide-resistant weeds are a growing concern globally; in response, new herbicide resistance traits are being inserted into crops. Isoxaflutole-resistant soybean [ Glycine max (L.) Merr.] will provide a new mode of action for use in this crop. Ten experiments were conducted over a 2-yr period (2017, 2018) to determine herbicide interactions between isoxaflutole and metribuzin on soybean injury, weed control efficacy, and soybean yield on a range of soil types. Soybean leaf-bleaching injury caused by isoxaflutole was most severe at sites with higher levels of rainfall after application. Control of weed species with isoxaflutole (52.5, 79, and 105 g ai ha −1 ) and metribuzin (210, 315, and 420 g ai ha −1 ) differed by site based on amount of rainfall after application. At sites where there was sufficient rainfall for herbicide activation, isoxaflutole at all rates controlled common lambsquarters ( Chenopodium album L.), Amaranthus spp., common ragweed ( Ambrosia artemisiifolia L.), and velvetleaf ( Abutilon theophrasti Medik.) >90%; metribuzin at all rates controlled Amaranthus spp. and witchgrass ( Panicum capillare L.) >80%. Control of every weed species evaluated was reduced when there was limited rainfall after herbicide application. The co-application of isoxaflutole + metribuzin resulted in additive or synergistic interactions for the control of C. album, Amaranthus spp., A. artemisiifolia, A. theophrasti, Setaria spp., barnyardgrass [ Echinochloa crus-galli (L.) P. Beauv], and P. capillare . Isoxaflutole and metribuzin can be an effective management strategy for common annual broadleaf and grass weeds in Ontario if timely rainfall events occur after herbicide application.